P-231 Using volunteers for bedside companions to support the concept of 'being there' at end of life. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Butler, Jenny
Abstract : Background: 'Being with' dying people is an integral part of nursing (Tornoe, Danbolt, Kvigne, Sorlie, 2014), with hospices best placed to holistically achieve this (Gomes & Higginson, 2008). However, an increasing demand of patients with complex end of life care and support needs, without requisite increase in funding, means the future challenges facing hospices are considerable (Commission into the Future of Hospice Care, 2012). The value of volunteers supporting people at end of life has now been widely recognised as a response to these challenges (Commission into the Future of Hospice Care, 2012; Radbruch & Payne, 2009). As hospice nurses identify less availability to sit with dying patients and their families, support was sought from a successfully established volunteer-led bedside companion scheme. Aim: To deliver innovative experience-led training to hospice volunteers: giving them confidence to visit and support patients in the hospice inpatient unit, particularly at end of life. Service will be closely monitored and evaluated to inspire future expansion. Methods: May 2018: met with Volunteer Communications Tutor for initial consultation and model planning; June 2018: Scoping for volunteers; July 2018: Focus group with hospice multidisciplinary staff; Aug–Oct 2018: Final volunteer recruitment; Sept 2018: Staff awareness sessions; Nov 2018: volunteer training delivered by Volunteer Communications Tutor. Volunteers visit local established bedside companion scheme to 'shadow'; Jan 2019: Service begins, comprising of mostly rostered scheduled sessions with a written summary recorded and reviewed by ward Sister. Six–weekly debriefing/supportive sessions between volunteers and staff are on–going. Results: 8 volunteers recruited. Pilot from January – end April 2019; 81 shifts; 257 visits; 41 patients; Taking 114 hours; Positive qualitative data collected from volunteers, inpatient staff and patients. Conclusion: Oakhaven's response to the challenges of a changing health and social care landscape by empowering volunteers with the skills to 'be with' hospice patients, as suggested by literature, has shown to be supportive to inpatient staff and patients. Future training sessions will widen the scope of available bedside companion support.